Origins of gender norms: Sibling gender composition and women's choice of occupation and partner - Anne Ardila Brenøe (University of Zurich, Department of Economics, 2018)
I examine how one central aspect of the childhood family environment - sibling gender composition - affects women's gender conformity, measured through their choice of occupation and partner. Using Danish administrative data, I causally estimate the effect of having a second-born brother relative to a sister for first-born women. The results show that women with a brother acquire more traditional gender norms with negative consequences for their labor earnings. I provide evidence of increased gender-specialized parenting in families with mixed-sex children, suggesting a stronger transmission of traditional gender norms. Finally, I find indications of persistent effects to the next generation of girls.
Keywords: I2; J1; J3; 330; Gender identity; sibling gender; occupational choice; family formation